Novel computational methods for the study of compliant-wall fluid-structure interaction - Kapor, Jarrad Stephen (Curtin University, 2012)
Applying compliant-wall coatings to otherwise rigid surfaces can delay the onset of laminar-turbulent transition and offer marked reductions in skin-friction drag and energy consumption, particularly in marine applications.However, the complex dynamics that result from the coupling of fluid and structure give rise to system instabilities that may prevent drag-reductions in engineering applications.A computational method is developed to study such systems and aid the design of compliant-wall technologies.